Simetria na Educação Básica a partir de uma perspectiva artística - Pereira, Stefhani Emiliani Vicente (Universidade Federal de São Carlos, 2024)
In this work, the aim is to provide a reflection on symmetry in Basic Education, emphasizing the relevance of the dialogue between Symmetry and Art for the teaching and learning process. In order to achieve this goal, an analysis of the changes related to symmetry concepts over time will be carried out. Subsequently, a theoretical discussion regarding the properties and concepts employed in symmetry will be structured, followed by an investigation into how this topic is approached in the school context. Thus, the perspective adopted to connect these themes involves the analysis of the artworks of the artist Maurits Cornelis Escher, whose compositions exhibit numerous geometric transformations. Additionally, a lesson plan will be developed to address this theme in the school setting, analyzing in practice the potential difficulties and learning experiences that students may encounter when exploring symmetry concepts through interaction with artistic resources.
Symmetry in Basic Education from an artistic perspective
Keywords: Simetria; Matemática; Arte; Educação básica; Escher; Symmetry; Mathematics; Arts; Basic education; CIENCIAS EXATAS E DA TERRA::MATEMATICA